Factors Related to Participation at the Elderly Integrated Service Post in Koeloda Health Center Golewa District Ngada Regency - Nguku, Marianus; Riwu, Yuliana Radja; Landi, Soleman (Timorese Journal of Public Health, 2022)
The Elderly Posyandu is a community-based health service unit built on the idea of ​​the community and the interests of the elderly. Posyandu activities for the elderly aim to provide opportunities for them to obtain basic health services, so that they can maintain their quality of life.The problems that exist in the posyandu for the elderly are the lack of visits by the elderly at the posyandu for the elderly, the distance from the house is far and the lack of knowledge of the elderly about the posyandu for the elderly. This study aims to analyze the factors related to the participation of the elderly at the posyandu for the elderly in the Koeloda Health Center work area, Golewa District, Ngada Regency in 2020. This study is an analytical survey research using a case control design. The population in this study were all elderly people in the working area of ​​the Koeloda Public Health Center, with a population of 1050 and the number of samples in this study were 38 case samples and 38 control samples selected using the simple random sampling method. The analysis was carried out bivariately using the chi square test. Based on the results of statistical analysis tests, it is known that there is a relationship between family support and elderly participation in the elderly posyandu (p = 0.00); (OR=3.399), and there is a relationship between the distance from the house and the participation of the elderly at the posyandu for the elderly (p=0.001); (OR = 6.067), while the variable that has no relationship is the level of education (p = 0.169). It is recommended to provide counseling and information to the elderly and their families to always encourage the elderly to always be actively involved in the posyandu for the elderly.